Argentine Adaptation and Validation of a Short Version of the Positive Parenting Scale (E2p) - Vargas-Rubilar, Jael (2020)
Background: Positive parenting is characterized by promoting healthy relationships in the family based on parental responsibility to ensure children’s rights and optimize their potential development and well-being. Given the importance of this topic for the good development of children, it is essential to have adequate instruments for its evaluation. Objective: to adapt to and validate in the Argentine population a short version of the Positive Parenting Scale (E2p) by Gómez and Muñoz (2014). Method: the scale was administered to a sample of 546 fathers and mothers (age: M = 38.54; SD = 6.37). The functioning of the items was studied, confirmatory factor analyses were carried out to establish whether the factor structure of the short form remained stable with respect to the complete form, and the internal consistency of the test was analized. Results: the proposed factorial model was tested through a confirmatory factor analysis (CFA) with the unweighted least squares (ULS) method, which indicated a very satisfactory fit of the abbreviated model. The internal consistency of the test was adequate for the full scale and dimensions. Conclusions: finally, the findings, limitations and future lines of research are discussed. Authorship contribution JVR: data collection and processing, data analysis and general writing of the manuscript (introduction, method, results and discussion). VL: methodological design of the study, analysis of data, results, discussion and general review of the manuscript. MCR: introduction, methodological design of the study and final review of the manuscript.